Teachers’ Perspective on Early Childhood Education Initiative in Public Sector Schools - Nuzhat Iqbal,; Ahmad Bilal, (JECCE, 2024)
Early Childhood Education promotes development for children through learning related activities to foster development of their cognitive, emotional, social and physical aspects. Since early childhood education encompasses from below eight years, this has a great impact on the children. The School Education Department in Punjab is equally working for the enhancement and expansion of ECE opportunity. This research aimed at evaluating teachers' perspectives on early childhood education initiative. For this reason, Qualitative research method was employed. Phenomenological research design was used with the assumption of providing observation of the teachers engaged in ECE initiative in Punjab. Qualitative data were obtained through face-to-face interviews with six participants selected by purposive sampling technique. The results highlighted the fact that overall, the teachers had a positive attitude and awareness about ECE and its contribution in laying as the foundational stage of education. However, issues with curricular equity, standardization of resource distribution, teachers’ training and program support were found out. The study suggests periodic training for teachers and financial support for ECE programs to enhance children's skills. Focus on teachers’ training and duration of training may be enhanced. Parental involvement may also be increased in parent-teacher meetings and prioritize the health, hygiene and safety of children.